Investigation of mechanical and metallurgical properties of commercially pure titanium grade 2 tube-to-tubesheet joints - Ahmad Al Tamimi; Dinu Thomas Thekkuden; Abdel-Hamid Ismail Mourad; Mohammad Alkhedher (Scientific Reports)
Abstract The present study investigated the structural integrity of three categories of Titanium Grade 2 based tube and tubesheet joints manufactured using welding, roller expansion and hybrid welding cum roller expansion process, to evaluate their mechanical performance and reliability in shell and tube heat exchangers applications. The influence of Tungsten inert gas welding and three tube expansion percentages (4%, 6%, and 8%) on the metallurgical and mechanical performance of the joints are extensively discussed. The findings showed that α′-phase was dominant in the weld zone and the heat affected zone with no noticeable signs for β-phase remnants in the mentioned zones. In addition, microstructural analysis on the expanded joints showed a direct relationship between the expansion percentage and the reduction of grains size near the roller expander in the expanded zone, while grains in transition and unexpanded zones experienced an insignificant impact due to expansion at both tube’s surfaces. The macroscopic studies revealed that the minimum leak path of the welded joint was satisfactorily greater than two-third of the tube wall thickness, indicating a sufficient sealing performance to prevent possible leakage at the joint region. The tube pull-out test showed that the tube pull-out loads were greater than the maximum allowable axial load for all the cases considered, confirming that the manufactured joints could endure axial loads that exceed the standard limits. Moreover, the weld region was found to be the hardest region in Vicker’s hardness test due to the dominance of the α′-phase, with a maximum hardness of 173.6 HV. These findings suggest that the provided joints’ manufacturing framework ensure reliable Titanium-based joints for critical shell and tube heat exchangers applications.